2007
DOI: 10.1111/j.1365-2133.2007.08113.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide analogue 14S24 selectively recovers perturbed human skin barrier

Abstract: Cutaneous microdialysis can serve as a useful tool for the evaluation of skin barrier recovery by topical formulations ex vivo whereas TEWL may not be an appropriate measure of skin barrier function in such studies. The excellent barrier repair activity of 14S24 could be beneficial in skin disorders with ceramide deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 55 publications
0
26
0
4
Order By: Relevance
“…Theophylline and indomethacin were selected as the model permeants having different molecular weights (molecular weight = 180 and 357 g/mol, respectively), lipophilicity (log p = -0.1 and 3.7, respectively), ionization constants (pK a values of theophylline are 1.7 and 8.8 and that of indomethacin is 4.5) and flux values through the porcine skin (1.4 and 0.26 g/cm 2 /h, respectively). Moreover, the permeability of theophylline proved to be a good marker of the skin barrier function [12,35] with higher sensitivity than transepidermal water loss [13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theophylline and indomethacin were selected as the model permeants having different molecular weights (molecular weight = 180 and 357 g/mol, respectively), lipophilicity (log p = -0.1 and 3.7, respectively), ionization constants (pK a values of theophylline are 1.7 and 8.8 and that of indomethacin is 4.5) and flux values through the porcine skin (1.4 and 0.26 g/cm 2 /h, respectively). Moreover, the permeability of theophylline proved to be a good marker of the skin barrier function [12,35] with higher sensitivity than transepidermal water loss [13] .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously studied ceramide analogues based on simple L -serine esters. Compound 14S24, having the same chain length as ceramide NS, was able to repair both porcine [12] and human skin barrier disrupted by various model insults [13] . On the other hand, compound 12S12, having the same polar head but shorter chains, acted as a permeation enhancer [14] .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the use of CER-containing cream showed a significant improvement of erythema, pruritus and fissuring compared with controls. Hence, there are some commercially available formulations intended for the direct replenishment of SC lipids in the SC, such as Lipobase® Repair Cream (Astellas Pharma Europe, Prague, Czech Republic), which contains CER[NS], CHOL and FFAs and is prescribed to moderate-to-severe dry skin conditions such as AD, irritant and allergic contact dermatitis and chronic hand eczema [96]. Other commercial formulations in the market which contain CERs are CeraVe®, TriCeram®, Atopiclair® and MimyX® Creams.…”
Section: Skin Diseases and Sc Lipid Substitution Therapymentioning
confidence: 99%
“…Vavrova et al [96] investigated the role of a cream containing a CER[NS] analogue, N-tetracosanoyl-( L )-serine tetradecyl ester (fig. 5; formed by replacement of the allylic hydroxyl NS by an ester group), on the barrier function of the skin.…”
Section: Skin Diseases and Sc Lipid Substitution Therapymentioning
confidence: 99%
“…In fact, preliminary studies using topical lipid mixtures containing, among other things, ceramides, pseudoceramides or other lamellar phase-forming lipids have shown favorable results in treating dry skin and atopic dermatitis [67,68,69,70]. …”
Section: Future Directionsmentioning
confidence: 99%